Materials and processing technology II special topic volume with peer reviewed papers only - Chinakhov, D. A. (Materials science forum ;, 2018)
This special issue contains research papers on modern technologies for obtaining and processing materials, additive technologies and technologies of welded joints, computer technologies for engineering tasks in materials science. The book is intended for a wide range of specialists engaged in the development and production of heavy-duty metal structures, as well as students, undergraduates, graduate and postgraduate students of technical colleges and universities.